Refractory Thrombocytopenia Responds to Octreotide Treatment in a Case of Evans Syndrome with Gastric Neuroendocrine Tumor - Kocfa Chung-Delgado; Alejandro Revilla-Montag; Sonia Guillén-Bravo; Hugo Ríos-Díaz; José C. Alva-Muñoz (Case Reports in Hematology)
A 37-year-old woman with history of Evans Syndrome with poor response to high-dose corticoid treatment presented to the emergency department with gastrointestinal and vaginal bleeding. The patient was later diagnosed with severe thrombocytopenia and a stage G1, well-differentiated gastric neuroendocrine tumor, confirmed by a biopsy. A total gastrectomy was performed to eradicate the tumor. After being treated with a total splenectomy for her Evans Syndrome with no clinical or laboratory improvement, she began regular treatment with octreotide on the basis of a possible hepatic metastasis. Days after the initiation of the octreotide, an increase in the platelet count was evidenced by laboratory findings, from 2,000 platelets/mm3 to 109,000 platelets/mm3. Weeks later, the hepatic metastasis is discarded by a negative octreotide-body scan, and the octreotide treatment was interrupted. Immediately after the drug interruption, a progressive and evident descent in the platelet count was evidenced (4000 platelets/mm3). The present case report highlights the possible association between octreotide treatment and a severe thrombocytopenia resistant to conventional treatment.